Advances in enzyme technology - Larroche, Christian; Pandey, Ashok; Singh, Ram Sarup; Singhania, Reeta Rani (Amsterdam, Netherlands Elsevier, 2019)
Biomass, Biofuels and Biochemicals: Advances in Enzyme Technology provides state-of-the-art information on the fundamental aspects and current perspectives in enzyme technology to graduate students, postgraduates and researchers working in industry and academia. The book provides information about the use of enzyme technology as an important tool for biotechnological processes, including food, feed, fuels, textiles, paper, energy and environmental applications. The search for improvements in existing enzyme-catalyzed processes dictates the need to update information on various enzyme technologies. The book gives a snapshot of current practice and research in the area of enzyme technology.
Microbial Enzymes - An Overview / Ram Sarup Singh, Taranjeet Singh and Ashok Pandey -- Isolation and Purification of Industrial Enzymes : Advances in Enzyme Technology / Soumya Mukherjee -- Enzyme Kinetics and Modeling of Enzymatic Systems / Emmanuel M. Papamichael, Haralambos Stamatis, Panagiota-Yioland Stergiou, Athanasios Foukis, Olga A. Gkini -- Thermodynamics of Enzyme-Catalyzed Reactions / Juan Carlos Aledo and Miguel Ángel Medina -- Enzymes in Green Chemistry : The State of the Art in Chemical Transformations / Eliane Pereira Cipolatti, Martina Costa Cerqueira Pinto, Rosana Oliveira Henriques, José Carlos Costa Da Silva Pinto, Aline Machado De Castro, Denise Maria Guimarães Freire, Evelin Andrade Manoel -- Enzyme Nanocarriers / Fei Peng, Hang Yin, Shi-Lin Cao, Wen-Yong Lou -- Immobilized Enzymes and Their Applications / Maximiliano L. Cacicedo, Ricardo M. Manzo, Sofía Municoy, Horacio L. Bonazza, German A Islan, Martín Desimone, Martin Bellion, Enrique J. Mammarella, Guillermo R. Castro -- Enzyme-Based Biosensors and Their Applications / Yuan-Cheng Zhu, Li-Ping Mei, Yi-Fan Ruan, Nan Zhang, Wei-Wei Zhao, Jing-Juan Xu, Hong-Yuan Chen -- Enzymes as Diagnostic Tools / Ram Sarup Singh, Taranjeet Singh, Ashish Kumar Singh -- Enzymes as Analytical Tools for the Assessment of Food Quality and Food Safety / Kamaljit Kaur, Pragati Kaushal -- Metabolic Engineering of Enzyme-Regulated Bioprocesses / Anshula Sharma, Ram Sarup Singh, Gaganjot Gupta, Tawseef Ahmad, Baljinder Kaur -- Enzyme Engineering / Kashyap Kumar Dubey, Avijit Pramanik, Ankush, Khushboo, Jyoti Yadav -- Recombinant Enzymes in the Food and Pharmaceutical Industries / Daniela Trono -- Chimeragenesis for Biocatalysis / Pedro Dinis, Benjamin Nji Wandi, Thadée Grocholski, Mikko Metsä-Ketelä -- Metagenomics in the Search for Industrial Enzymes / Tawseef Ahmad, Ram Sarup Singh, Gaganjot Gupta, Anshula Sharma, Baljinder Kaur -- Computational Resources and Techniques in Enzyme Research / Pragya Priyadarshini, Balvinder Singh -- Thermostable Enzymes for Industrial Biotechnology / Sunny Sharma, Surbhi Vaid, Bilqeesa Bhat, Satbir Singh, Bijender Kumar Bajaj.
Includes bibliographical references and index.
Electronic reproduction
Keywords: Enzymes -- Biotechnology; Electronic books